PENGARUH LATIHAN SLOW DEEP BREATHING TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TULEHU TAHUN 2020 - Abdul Thalib; Gresye Tutuarima (STIKES Pasapua Ambon, 2021)
Introduction: Slow Deep Breathing is a non-pharmacological action for hypertensive patients that can lower blood pressure. Hypertension is a condition of increasing a person’s blood pressure above normal which can result in increased morbidity and mortality. Objective: To determine the effect of slow deep breathing exercise on blood pressure in hypertensive patients in the Tulehu Health Center Work Area. Methods: What was used in this study was a pre-experimental design with a one-group pretest-posttest design. The independent variable is slow deep breathing exercise and the dependent variable is blood pressure. The research was conducted in November 2020. The sample for this research was selected using a non-probability sampling technique with a purposive sampling approach and a total of 40 samples. The statistical test used was Wilcoxon a = 0.005. Results: Shows that there is a relationship between slow deep breathing exercises and a decrease in blood pressure in hypertensive patients in the Tulehu Health Center Work Area in 2020, namely p = 0.000 <0.05. Conclusion: There is an effect of slow deep breathing exercise on reducing blood pressure in hypertensive patients in the Working Area of the Tulehu Health Center in 2020